The Effects of Arbuscular Mycorrhizal Fungal Colonisation on Nutrient Status, Growth, Productivity, and Canker Resistance of Apple (Malus pumila) - Berdeni, Despina; Cotton, T. E. A.; Daniell, Tim J.; Bidartondo, Martin I.; Cameron, Duncan D.; Evans, Karl L. (Frontiers in Microbiology, 2018)
We assess whether arbuscular mycorrhizal fungi (AMF) improve growth, nutritional status, phenology, flower and fruit production, and disease resistance in woody perennial crops using apple (Malus pumila) as a study system. In a fully factorial experiment, young trees were grown for three years with or without AMF (Funneliformis mosseae and Rhizophagus irregularis), and with industrial standard fertiliser applications or restricted fertiliser (10% of standard). We use two commercial scions (Dabinett, Michelin) and rootstocks (MM111, MM106). Industrial standard fertiliser applications reduced AMF colonisation and root biomass, potentially increasing drought sensitivity. Mycorrhizal status was influenced by above ground genotypes (scion type) but not rootstocks, indicating strong interactions between above and below ground plant tissue. The AMF inoculation significantly increased resistance to Neonectria ditissima, a globally economically significant fungal pathogen of apple orchards, but did not consistently alter leaf nutrients, growth, phenology or fruit and flower production. This study significantly advances understanding of AMF benefits to woody perennial crops, especially increased disease resistance which we show is not due to improved tree nutrition or drought alleviation. Breeding programmes and standard management practices can limit the potential for these benefits